Abundance of the life stages of three Calanus species and Metridia longa during Polarstern cruise ARK-XXVI/3 (PS78, TRANSARK) - Ksenia Nikolaevna Kosobokova; Hans-Juergen Hirche; Russell R Hopcroft; Elizaveta A Ershova; Astrid Cornils (PANGAEA, 2023)
Abundances of the life stages of the three Calanus species (Calanus finmarchicus, Calanus glacialis and Calanus hyperboreus) and Metridia longa was calculated in the Arctic Ocean during Polarstern cruise ARK-XXVI/3. Samples were taken with the Multinet maxi (Hydrobios, Kiel), which is equipped with nine nets (mesh size: 150 μm).
In: Cornils, Astrid; Hirche, Hans-Juergen (2021): Collection of zooplankton abundance data from the Arctic Ocean during POLARSTERN cruises [dataset publication series]. Alfred Wegener Institute, Helmholtz Centre for Polar and Marine Research, Bremerhaven, PANGAEA, https://doi.org/10.1594/PANGAEA.926084